THE PERSONALITY FACTOR IN ACCOUNTING SUCCESS. - Frederick, Marvin L. (The Accounting Review, 1938)
To some people an accountant is still a human adding machine. It may be true that his success is dependent to a considerable extent upon his aptitude for handling figures, but the leading positions in this profession rest in the hands of those who combine this aptitude with an even more important qualification, the ability to negotiate. Students specializing in accounting are, for the most part, woefully ignorant of the necessity of developing this ability and therefore concentrate on the theory as found in books and in problems to the exclusion of experience in making contacts with individuals. Students who have a natural aptitude for dealing with people sometimes avoid accounting as a career because they are not sufficiently familiar with the satisfaction, which an accountant experiences in the way of contacts. Therefore, many young men who would succeed as accounting executives select other careers because they want jobs in which they meet people rather than those pore over figures all day long.